Enhancing transdisciplinary research through collaborative leadership in an ecohealth approach for the control of zoonosis in Yunnan province, China - Guorong Yang; Shibiao Yang; Unger, Fred; Xiangdong Yang; Wengui Li; Jing Fang; Gilbert, Jeffrey (Khon Kaen University, 2013)
Like other parts of China, in Yunnan Province top-down administrative approaches which usually focus on sector or discipline are responsible for the prevention and control of zoonoses. Animal and human health operating through their own independent systems. Experience shows that to control zoonoses more effectively, horizontal co-operation between various disciplines has to be enhanced. Here we present experiences and challenges in implementation of an Ecohealth project led by the International Livestock Research Institute (ILRI) with the objective to better management Brucellosis and Toxoplasmosis in the Yunnan province of China. In accordance with to the principles of an Ecohealth approach, animal science, veterinary, public health experts from five provincial institutions, practitioners, and representatives from the Department of Health & Department of Agricultural were involved in the project. Research activities consisted of a literature review, a households/on-farm survey using qualitative (FGD and interviews) and quantitative tools (questionnaires) to collect data on risk factors and perception on these zoonoses from potential risk groups. To build transdiciplinary relations between participating institution and the limited Eco-Health capacity of partners were seen as the key challenges. Those challenges were overcome through multiple leaders and champions who collaborate on key tasks, ensuring that each separate unit builds commitment and buy-in to the overall transdisciplinary mission. Essential for the collaboration between potentially interested partners was the identification of a common research topic. Enforced continued communication efforts by the coordinating institute throughout the entire project were another condition for success. Crucial was also the support by Agriculture Department and Health Department of Yunnan. Steps and mechanism along the implementation of this project, such as jointly developed project framework, research tools and implementation were documented and will be shared. It is anticipated that this project will guide other partners of China to further recognize the Eco-Health concept and how to implement it.